The role of the sports coach in developing athlete capacity for transition to retirement - Agnew, Deborah; Pill, Shane (Frontiers in Sports and Active Living, 2025)
The transition from high performance athlete to retirement can present significant challenges for athletes and requires support to navigate the process successfully. Given the central role of the coach in athletes' lives, we are suggesting expanding the perspective on athlete-centre coaching to include life and career transitions thereby extending its temporal scope beyond competitive performance. While the holistic development of the athlete is emphasised, much of the literature on athlete-centred coaching focuses on preparing the athlete through a player-centred approach for competition rather than the role of the coach in athlete transition to retirement. Therefore, this perspective piece expands the notion of coaching life skills in athlete-centred coaching by Griffen and colleagues to include the important role of the coach in developing athlete capacity for transition to retirement.